Capsule immobilisation of sulphate-reducing bacteria and application in disarticulated systems - Sanyahumbi, Douglas (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2004)
Biotechnology of sulphate reducing bacteria has developed rapidly in recent years with the recognition of their extensive and diverse biocatalytic potential. However, their application in a number of areas has been constrained due to problems including poor cell retention within the continuous bioprocess reactor environment, and contamination of the treated stream with residual organic feed components and cell biomass. These problems have so far excluded the application of biological sulphate reduction in the treatment of 'clean' inorganic waste streams where components such as sulphate, acidity and heavy metal contamination require treatment. This study investigated the effective immobilisation of sulphate reducing bacterial cultures and proposed that the disarticulation of the electron donor and carbon source supply using such systems would create the basis for their application in the treatment of 'clean' inorganic waste streams. A functional and stable sulphate reducing culture was selected and following evaluation using a number of techniques, was immobilised by encapsulation within a calcium-alginate-xanthum gum membrane to give robust capsules with good sulphate reduction activity. The concept of disarticulation was investigated in a swing-back cycle where the carbon source was excluded and the electron donor supplied in the form of hydrogen gas in a continuous up-flow capsule-packed column reactor. Following a period of operation in this mode (4-12 days), the system was swung back to a carbon feed to supply requirements of cell maintenance (2-3 days). Three types of synthetic 'clean' inorganic waste stream treatments were investigated, including sulphate removal, neutralisation of acidity and heavy metal (copper and lead) removal. The results showed: "¢ Sulphate removal at a rate of 50 mg SOâ‚„Â²â »L/day/g initial wet mass of capsules during three 4-day cycles of electron donor phase. This was comparable to the performance of free cell systems; "¢ Neutralisation of acidity where influent pH values of 2.4 and 4.0 were elevated to above pH 7.5; "¢ Copper removal of 99 and 85 % was achieved with initial copper concentrations of 2 and 60 mg/L respectively; "¢ Percentage lead removal values of 49 and 78 % were achieved; This first report on the application of the concept of capsular immobilisation and disarticulation in the treatment of 'clean' inorganic waste streams will require future studies in order to extend the development of the full potential of the concept.
Keywords: Sulfur bacteria; Water -- Purification -- Biological treatment